Initial Effects of Mandatory XBRL Adoption across the Indonesia Stock Exchange`s Financial Information Environment - Muhammad Zamroni; Y Anni Aryani (University of Merdeka Malang, 2018)
This research aims to investigate the initial effects of mandatory eXtensible Business Reporting Language (XBRL) across the Indonesia Stock Exchange`s financial information environment. Financial information environment is measured by event return volatility, absolute cumulative abnormal return, change in standard deviation of returns, abnormal bid-ask spread, and abnormal trading volume. Comparing the effects of pre- and post- XBRL period, we provide evidence that there is no significant implication in the first year of XBRL adoption. It is showed that event return volatility, changes in the standard deviation of returns, and abnormal bid-ask spread was not reduced in the post- XBRL period. On the other hand, it was able to intensify the stock trading volume which noted by the increased abnormal trading volume after mandatory XBRL policy was enacted.JEL Classification: G31; G32; G34DOI: https://doi.org/10.26905/jkdp.v22i2.2092